2022
DOI: 10.1093/bjs/znac242.006
|View full text |Cite
|
Sign up to set email alerts
|

O006 A randomised trial of normothermic machine perfusion versus static cold storage in donation after circulatory death renal transplantation

Abstract: Introduction Kidneys from donation after circulatory death (DCD) donors are more susceptible to cold storage (CS) injury and have a high risk of delayed graft function (DGF). This trial is the first to compare normothermic machine perfusion (NMP) to conventional CS in DCD kidney transplantation. Methods In a multicentre randomised control trial, DCD kidneys were randomised to either NMP or CS. NMP kidneys were perfused for 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…10,11 In DCD kidney, transplant of a 1-h period of NMP at the end of SCS did not reduce the rate of DGF compared to SCS alone. 32 The efficacy of NMP for a longer period or continuous (initiated at the donor hospital) NMP needs to be tested for future trials.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In DCD kidney, transplant of a 1-h period of NMP at the end of SCS did not reduce the rate of DGF compared to SCS alone. 32 The efficacy of NMP for a longer period or continuous (initiated at the donor hospital) NMP needs to be tested for future trials.…”
Section: Discussionmentioning
confidence: 99%
“…Hosgood et al also contacted the only randomized control trial investigating the use of NMP. In a multicentered randomized control trial of 338 DCD donor kidney transplants, they found no significant difference in DGF rates (OR 1.13, 95% CI 0.69–1.84, P = 0.62) or secondary outcomes, including PNF, 1-year graft function, graft survival, and acute rejection within 1 year [45 ▪▪ ].…”
Section: Oxygenated Normothermic Machine Perfusionmentioning
confidence: 97%
“…Amongst all three groups, tubular injury was equally low. These studies highlight the potential feasibility of NMP use for a duration longer than 8 h. Recently in the first randomized controlled 2 to compare traditional SCS ( n = 168) with SCS + 1 h NMP ( n = 170) in DCD human kidney transplantations, Hosgood et al 50 demonstrated that 1 h of perfusion does not reduce the occurrence of DGF. Kidney repair and reconditioning…”
Section: Potential Clinical Use Of Kidney Nmpmentioning
confidence: 99%